Pengaruh Pengunaan Alat Peraga Origami Bilangan Real dan Observasi Partisipan terhadap Self Eficiency Diri Siswa SD/MI dalam Mengerjakan Materi Operasi Hitung Bilangan Real - Nanda Elza; Siti Aisyah Harahap; Dinda Aisyah Nst; Hani Nabila Humaira (Journal on Education, 2023)
To build a civilization that is able to understand, develop, manage, and apply science and technology, education is a very important instrument. Due to low self-efficacy, educational outcomes cannot be adapted to contemporary demands, which has a negative impact on student achievement. Learning outcomes in question, especially in mathematics, must require an understanding of the various factors that influence learning success. In general, both internal and external factors—which come from students—have an influence on how well they learn mathematics. Self-efficacy, curiosity, and study habits are just a few examples of the psychosocial elements that students bring themselves. Because elementary school children are very lazy to learn to count by using media such as origami to learn natural numbers, teachers have low self-efficacy in influencing students' mathematics learning. In this study, classroom action research (PTK) was used to conduct research on increasing students' self-efficacy by using fourth-grade children in the city of Medan as research subjects. The self-efficacy questionnaire was used as a research instrument. student observations on math exams. The planning phase, the promotion phase, and the observation phase are all used in data analysis. This implies that a scientific approach can increase student success and self-efficacy.